The Epistolary Fictions of a Chronicle - Rodrigues, Leandro Garcia (Opiniães, 2020)
The novel Chronicle of the Murdered House, the maximum work by Lúcio Cardoso, has numerous possibilities of meaning and interpretation; one of them, certainly, concerns about its structure of epistolary fiction. This article aims to analyze critically the dimension of epistolary fiction in the economy of this novel: plots, organization, narrative focus, and the countless letters exchanged by the characters, which provides an outstanding differential to the work of the Curvelan author.